Are children from different countries exposed to diverse emotions in storybooks? Comparative study between Chile and the United States. Issue 4 (28th February 2020) - Farkas, Chamarrita; Gerber, Denise; Mata, Cecil; Santelices, María Pía
Abstract: Children's storybooks are relevant resources for references to different emotions, both positive and negative, and provide an excellent opportunity for adults and children to discuss them, thereby promoting children's comprehension of their own and others' inner worlds. However, we know little about the emotions present in children's stories and their frequency. This study investigated references to emotions in children's storybooks for preschoolers in Chile and the United States to analyze their characteristics and the similarities and differences between the two countries. References to specific emotions in the texts of 80 children's storybooks (40 for each country) were coded according to the categories of positive, negative powerless, and negative powerful emotions, and the specific emotions considered. The results revealed more references to positive and negative powerless emotions than to negative powerful emotions in storybooks from both countries, and happiness, fear, sadness, and anger were the predominant specific emotions referenced. For both countries, similar frequencies of references to specific emotions were observed, except for surprise, disappointment, and anger, which appeared more frequently in the Chilean storybooks than in the U.S. storybooks. These results are discussed considering the emotions to which young children are exposed and the implications of such exposure for children's socioemotional development.